Production of alpha-interferon in Lactococcus lactis - Bayat, Omid (2013)
Human interferon-a2b (IFN-a2b) is one of the members of IFN family and it is also one of the biopharmaceuticals used to cure diseases such as hairy cell leukemia, malignant melanoma, and chronic hepatitis (B and C). The majority of commercial products available in the market are obtained in E.coli. The high production of E. coli is in the form of inclusion body (IB) which has to pass through costly refolding steps and also complicated purification procedures for removing of lipopolysaccharide (endotoxin) are required. In contrast, recombinant IFN-a produced by L. lactis strain with GRAS status does not form IB and can be delivered at the mucosal level and does not require costly refolding steps and purification procedures. It can also be used as an adjuvant in designing new vaccines against viral infections. In this study, four recombinant L. lactis, MGIF (containing P32, a constitutive promoter), PNZ, PNHIF, PNZUSPIF (containing Pnis, an inducible promoter) were constructed for the expression of IFN-alph 2b. The production of IFN-a2b was confirmed by ELISA and western blotting and the plasmid stability test showed that the recombinant plasmids were stable in the strains even after 100 generations. The effect of different carbon sources (glucose,sucrose and lactose), nisin induction and incubation time in M17 medium on the amount of production were also tested. The results showed that the highest production was achieved in presence of glucose for all the recombinant strains and the best concentration of nisin induction for recombinant strains with Pnis promoter was at 30 ng/mL. In addition, the highest expression amount of IFN for MG1363 recombinant (MGIF) was at 9 hours of incubation and for NZ9000 recombinants (NZIF and NZUSPIF) was at 4.5 hours. Among the four recombinant strains, the highest production amount with the optimum conditions was achieved by recombinant NZ9000 harbouring SPusp45- IFN-a 2b gene (~0.27 ag/L). The expressed IFNs were subjected to bioactivity test and they showed acceptable bioactivity of 1.9×106 IU/mg. In conclusion, the results of this study proved that IFN-alpha 2b can be expressed in L. lactis with an acceptable level of bioactivity.